An energy transition pathway for Turkey to achieve 100% renewable energy powered electricity, desalination and non-energetic industrial gas demand sectors by 2050. (December 2017) - Kilickaplan, Anil; Bogdanov, Dmitrii; Peker, Onur; Caldera, Upeksha; Aghahosseini, Arman; Breyer, Christian
Graphical abstract: The purpose of this study is to design a 100% renewable energy transition scenario for Turkey for the time period of 2015–2050, with a special emphasis on the respective economics. The study aims to show how an optimum transition pathway can meet Turkey's electricity, water and non-energetic industrial gas demands in the mid- to long-term by a 100% renewable energy system. Highlights: Turkey's energy system can be powered solely by renewable energy. A 100% renewable energy system reduces fuel import dependency in Turkey. Solar PV plays a key role in a fully sustainable energy system by 2050. Energy transition costs 57.3 €/MW hel to 65.4 €/MW hel depending on the scenario. Sector integration brings several benefits into the system, such as cost reduction. Abstract: In this research, Turkey's energy transition towards 100% renewable energy (RE) until 2050 is analysed by using an hourly resolved model. Turkey is structured into seven geographical regions and all assumptions and data are collected and applied separately for the regions. The energy transition is simulated for two scenarios: a power sector scenario and power sector plus desalination and non-energetic industrial gas demand (integrated) scenario. Turkey has an enormous solar energy potential, which leads to an installed solar PV capacity of 287 GW (71% of total installed capacity) in the power scenario and 387 GW (73% of total installed capacity) in the integrated scenario in 2050. Solar PV and other installed RE systems are balanced by storage systems to increase the flexibility of the system. Levelised cost of electricity increased slightly in the power scenario, from a fossil fuel based system with 63 €/MW hel in 2015 to a fully RE-based system with 65.4 €/MW hel in 2050. The capacity mix in the power scenario entirely built for the assumptions of the year 2050 led to a cost of 51 €/MW hel, which can also be expected in the periods beyond 2050. In the integrated scenario, however, the costs decreased from 60.3 €/MW hel to 57.3 €/MW hel, mainly due to the benefit of sector coupling. A 100% RE system reduces energy import dependency and carbon emissions, while reducing the cost of energy supply.